2008
DOI: 10.1111/j.1582-4934.2008.00516.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells and their use as cell replacement therapy and disease modelling tool

Abstract: Mesenchymal stem cells (MSCs) from adult somatic tissues may differentiate in vitro and in vivo into multiple mesodermal tissues including bone, cartilage, adipose tissue, tendon, ligament or even muscle. MSCs preferentially home to damaged tissues where they exert their therapeutic potential. A striking feature of the MSCs is their low inherent immunogenicity as they induce little, if any, proliferation of allogeneic lymphocytes and antigen-presenting cells. Instead, MSCs appear to be immunosuppressive in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
91
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 138 publications
1
91
0
1
Order By: Relevance
“…Increasing evidence indicates that MSCs might constitute the target cell for transforming mutations responsible for sarcoma development, suggesting that MSCs/ASCs may become an instrumental tool in studies aimed at dissecting the pathogenesis and cellular origin of sarcomas [1]. It has been demonstrated that BM-mMSCs provided a permissive environment for tumoral transformation and sarcoma development mediated by several sarcoma-associated fusion genes [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidence indicates that MSCs might constitute the target cell for transforming mutations responsible for sarcoma development, suggesting that MSCs/ASCs may become an instrumental tool in studies aimed at dissecting the pathogenesis and cellular origin of sarcomas [1]. It has been demonstrated that BM-mMSCs provided a permissive environment for tumoral transformation and sarcoma development mediated by several sarcoma-associated fusion genes [2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…It is becoming evident that mesenchymal stem cells (MSCs) may be the target cell in which transforming mutations responsible for sarcoma development arise [1]. Several types of sarcomas have been reproduced in vivo on overexpression of specific fusion oncoproteins in bone marrow (BM)-derived mouse MSCs (mMSCs).…”
Section: Introductionmentioning
confidence: 99%
“…The onset and progression of hematological malignancies are in many cases dependent on mutual interactions between the leukemic blasts/plasma cells and BM stroma/MSCs, which provide survival and growth-promoting signals [8,95,96]. Interestingly, the fusion MLL-AF4 was recently found expressed in both BM-MSCs and leukemic blasts in 100% of infants suffering from pro-B ALL highlighting an unrecognized role of the BM milieu in the pathogenesis of this dismal infant leukemia [97].…”
Section: Mscs and Tumor Growthmentioning
confidence: 99%
“…Thus, cultures are heterogeneous in potency and it is likely that only a small MSC subset represents the bona fide multipotent stem cell population. The potential of MSCs for cell-based therapies relies on several key properties: (i) capacity to differentiate into several cell lineages; (ii) lack of immunogenicity; (iii) immunomodulatory properties; (iv) robust ex vivo expansion potential; (v) ability to secrete factors, which regulate cell proliferation, differentiation and migration and; (vi) homing ability to damaged tissues and tumor sites [8]. Due to these properties, MSCs are being used worldwide in a variety of clinical applications including tissue repair, treatment of graft-versus-host disease and autoimmune diseases and are being used as vehicles to deliver anti-cancer therapies [8].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) immunoregulatory effects and allogenic tolerance 1 led to investigations into the treatment of severe immune‐mediated diseases 2, which in turn attracted interest on anti‐inflammatory MSCs as a potential asthma treatment. However, the use of MSCs for asthma may face significant limitations.…”
mentioning
confidence: 99%